(untitled) (Journal of Global Accounting, 2023)
This study empirically examined the relationship between contemporary compensation schemes and corporate performance. In order to determine the relationship between contemporary compensation schemes and corporate performance, contemporary compensation schemes was proxy using; equity based compensation, profit based compensation, bonus based compensation and commission based compensation while corporate performance on the other hand was represented by Net Assets Per Share (NAPS). Four hypotheses were formulated to guide the investigation and the statistical test of parameter estimates was conducted using OLS regression model. The study employed Ex Post Facto design in the data analysis. Secondary data used for the study were obtained from the Nigerian Exchange Group Factbook and the Published Annual Financial Reports & Accounts of the entire 10 firms quoted under Oil and Gas Sector of NGX. The data used for the study spanned from 2017-2021. The findings generally indicated that equity based compensation (EBC), profit based compensation (PBC), bonus based compensation (BBC) and commission based compensation (CBC) exerted significant and positive influence on corporate performance (NAPS) in Nigeria at 5% level of significance. Based on this, the study concludes that contemporary compensation schemes positively improved firms’ performance in Nigeria. In lieu of this, the study suggests that organizations that want an enhanced performance should ensure that the company’s compensation system must include policies, procedures and rules that provide clear and unambiguous determination and administration of workers compensation. Hence the study contributed to knowledge by modifying existing models, introducing new variable and updating literature on the subject.